1988
DOI: 10.1055/s-0038-1646977
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Factor VIII in Human Hepatocytes in Culture

Abstract: SummaryAlthough several investigators have attempted to identify the site of synthesis of factor VIII (FVIII), the cellular species responsible for maintenance of plasma FVIII has not been clearly defined. Indications point at hepatocytes and certain endothelial cells. The present study investigated the FVIII coagulant antigen (VIII : Ag) of hepatocytes obtained by two-step collagenase digests of human liver pieces. Following Percoll gradient centrifugation, less than 1% of cells harvested were non-parenchymal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…In contrast, others have identified FVIII mRNA or FVIII:Ag in hepatocytes but not in LSECs . FVIII:Ag has also been detected in the supernatant of in vitro cultures of purified hepatocytes . Owing to these contradictory reports, it is currently unclear which liver cells produce FVIII in humans.…”
Section: Introductionmentioning
confidence: 95%
“…In contrast, others have identified FVIII mRNA or FVIII:Ag in hepatocytes but not in LSECs . FVIII:Ag has also been detected in the supernatant of in vitro cultures of purified hepatocytes . Owing to these contradictory reports, it is currently unclear which liver cells produce FVIII in humans.…”
Section: Introductionmentioning
confidence: 95%
“…Data on the synthesis and secretion of the haemostasis proteins from human hepatocytes in primary cultures remain very limited (Ingerslev et al , 1988; Mazzorana et al , 1991; Ferrini et al , 1997). Ingerslev et al (1988) found that lysates of freshly isolated and purified human hepatocytes contained and secreted FVIII. Mazzorana et al (1991) tested the reliability of their hepatocyte culture model using FV detection.…”
mentioning
confidence: 99%
“…9 Even within the liver, the cell type or types in which the FVIII is synthesized are not clearly established. 8,10 The synthesis of vWF has been demonstrated in endothelial cells and megakaryocytes, where it is stored in specialized vesicles: Weibel-Palade bodies (WPBs) and ␣-granules, respectively. 11,12 In the late trans-Golgi network, vWF is sorted into releasable dense-core granules.…”
mentioning
confidence: 99%
“…3 Organ transplantation studies in recent decades have identified that the liver, 4 as well as several extrahepatic sources of FVIII (lung, lymphatics, and spleen), [5][6][7] produces FVIII in humans and dogs with hemophilia A. Although FVIII synthesis by hepatocytes has been demonstrated, 8 end-stage liver disease is not associated with a decrease in plasma FVIII levels. 9 Even within the liver, the cell type or types in which the FVIII is synthesized are not clearly established.…”
mentioning
confidence: 99%